Benefits of Kalteng Berkah Scholarship, What's for and to Whom? (Evaluation of Scholarship Program Using a Transactional Model) - Bulkani, Bulkani; Kartini, Nurul Hikmah; Rahmaniati, Rita (International Journal of Universal Education, 2023)
Background: Based on the 2016-2021 Central Kalimantan Long Term Development Plan (RPJMD) contained in Regional Regulation Number 1 of 2017 (2), the vision of the Central Kalimantan provincial government is called Kalteng Berkah. "Kalteng Berkah" is an abbreviation for Central Kalimantan, which means dignified, graceful, religious, strong, fair, and harmonious. The Kalteng Berkah Program focuses on nine missions, including accelerating infrastructure development, increasing regional income, controlling inflation, alleviating poverty, and improving the quality of education and health. This mission gave birth to several programs, including the Central Kalimantan Berkah program in the field of education. Aim: Based on the technical guidelines for the Bidikmisi Kalteng Berkah program, this program aims to help the people of Central Kalimantan who need funding for their studies or to complete studies at universities. Method: This study used a transactional model program evaluation method. The paradigm was a mixed qualitative-quantitative paradigm. A qualitative approach was used to analyze the awardee's responses descriptively. Results and Dıscussion: the program has achieved the expected goals. In general, achieving objectives as perceived by the awardee indicates the program's success and may be used as consideration for policymaking to continue the program. Conclusion: By using the transactional evaluation model, we concluded that the Kalteng Berkah Scholarship program has been successfully implemented following the expected program objectives.